Oxidative Stress and Analysis of Selected SNPs of ACHE (rs 2571598), BCHE (rs 3495), CAT (rs 7943316), SIRT1 (rs 10823108), GSTP1 (rs 1695), and Gene GSTM1, GSTT1 in Chronic Organophosphates Exposed Groups from Cameroon and Pakistan - Mbah Ntepe, Leonel Javeres; Habib, Rabia; Judith Laure, Ngondi; Raza, Saqlain; Nepovimova, Eugenie; Kuca, Kamil; Batool, Sajida; Muhammad Nurulain, Syed (International journal of molecular sciences, 2020)
The detrimental effects of organophosphates (OPs) on human health are thought to be of systemic, i.e., irreversible inhibition of acetylcholinesterase (AChE) at nerve synapses. However, several studies have shown that AChE inhibition alone cannot explain all the toxicological manifestations in prolonged exposure to OPs. The present study aimed to assess the status of antioxidants malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH) (reduced), catalase, and ferric reducing antioxidant power (FRAP) in chronic OP-exposed groups from Cameroon and Pakistan. Molecular analysis of genetic polymorphisms (SNPs) of glutathione transferases (GSTM1, GSTP1, GSTT1), catalase gene (CAT, rs7943316), sirtuin 1 gene (SIRT1, rs10823108), acetylcholinesterase gene (ACHE, rs2571598), and butyrylcholinesterase gene (BCHE, rs3495) were screened in the OP-exposed individuals to find the possible causative association with oxidative stress and toxicity. Cholinesterase and antioxidant activities were measured by colorimetric methods using a spectrophotometer. Salting-out method was employed for DNA extraction from blood followed by restriction fragment length polymorphism (RFLP) for molecular analysis. Cholinergic enzymes were significantly decreased in OP-exposed groups. Catalase and SOD were decreased and MDA and FRAP were increased in OP-exposed groups compared to unexposed groups in both groups. GSH was decreased only in Pakistani OPs-exposed group. Molecular analysis of ACHE, BCHE, Catalase, GSTP1, and GSTM1 SNPs revealed a tentative association with their phenotypic expression that is level of antioxidant and cholinergic enzymes. The study concludes that chronic OPs exposure induces oxidative stress which is associated with the related SNP polymorphism. The toxicogenetics of understudied SNPs were examined for the first time to our understanding. The findings may lead to a newer area of investigation on OPs induced health issues and toxicogenetics.
Keywords: dospělí; Butyrylcholinesterase; butyrylcholinesterasa; katalasa; Acetylcholinesterase; Sirtuin 1; Female; glutathion; oxidační stres; Catalase; Glutathione; Adult; Organophosphorus Compounds; ženské pohlaví; mladý dospělý; jednonukleotidový polymorfismus; Adolescent; Glutathione S-Transferase pi; Oxidative Stress; GPI-vázané proteiny; lidé; glutathiontransferasa; Kamerun; interakce genů a prostředí; Polymorphism, Single Nucleotide; Glutathione Transferase; Cameroon; organofosforové sloučeniny; Gene-Environment Interaction; Male; acetylcholinesterasa; Malondialdehyde; GPI-Linked Proteins; Young Adult; Pakistan; vystavení vlivu životního prostředí; malondialdehyd; lidé středního věku; mužské pohlaví; Pákistán; glutathion-S-transferasa fí; Environmental Exposure; Middle Aged; mladiství; sirtuin 1; Humans